Digital public services and subjective well-being in rural China: health and multidomain lifestyle pathways in the cross-provincial Dabie Mountains region - Lei Jiang; Yuqiao Ma; Zihan Yang; Hao Li (Frontiers in Public Health, 2026)
Introduction Against the backdrop of China’s Digital Rural Development Strategy and the growing emphasis on integrated health, food-purchasing access, and lifestyle approaches to well-being, digital public services (DPS) are increasingly important for rural public health. However, little is known about the association between integrated DPS and subjective well-being (SWB) in geographically constrained mountainous regions or about the health- and lifestyle-related pathways underlying this association. Methods Using survey data from 1,287 rural residents across 26 counties in the Dabie Mountains Region, this study constructs comprehensive DPS and SWB indices using the entropy weight method and employs ordinary least squares as the baseline estimator, complemented by robustness checks and an instrumental-variable sensitivity analysis. Results The results show that DPS is positively associated with SWB, and the association remains stable across alternative specifications. The estimated coefficients are descriptively larger in the Anhui section, among low-income households, and among residents with lower education levels. Separate exploratory models yield evidence consistent with five potential indirect pathways: livelihood stability and income diversification, improved education and medical service quality, enriched cultural and social interaction, greater daily-life purchasing and delivery convenience, and improved integrated health and multidomain lifestyle behaviors, including physical activity, sleep quality, stress management, and digital health-tool use. Discussion These findings suggest that DPS may support rural well-being through service access, digital purchasing and delivery functions, and technology-supported multidomain health management, providing context-specific empirical evidence relevant to the design of integrated digital public service strategies in mountainous communities.